2014
DOI: 10.1377/hlthaff.2013.1359
|View full text |Cite
|
Sign up to set email alerts
|

Rates Of Major Obstetrical Complications Vary Almost Fivefold Among US Hospitals

Abstract: Of the approximately four million women who give birth each year in the United States, nearly 13 percent experience one or more major complications. But the extent to which the rates of major obstetrical complications vary across hospitals in the United States is unknown. We used multivariable logistic regression models to examine the variation in obstetrical complication outcomes across US hospitals among a large, nationally representative sample of more than 750,000 obstetrical deliveries in 2010. We found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 37 publications
0
44
0
Order By: Relevance
“…Previous research has shown that implementing maternal safety bundles for obstetric hemorrhage can effectively reduce severe maternal morbidity. 34 Further research is needed to validate our findings. We found two institutional characteristics associated with hospital performance in combined maternal and newborn outcomes-type of ownership and delivery volume.…”
Section: F I G U R Ementioning
confidence: 76%
“…Previous research has shown that implementing maternal safety bundles for obstetric hemorrhage can effectively reduce severe maternal morbidity. 34 Further research is needed to validate our findings. We found two institutional characteristics associated with hospital performance in combined maternal and newborn outcomes-type of ownership and delivery volume.…”
Section: F I G U R Ementioning
confidence: 76%
“…Consistent with prior studies on quality of maternity care, 2, 17 we chose three broad categories of maternal complications. Individual adverse outcomes are rare in obstetrics, so we chose broad categories to enable sufficient number of events and statistical power.…”
Section: Methodsmentioning
confidence: 99%
“…1 Recent studies have documented wide variation in hospital-level rates of obstetric procedures and complications 23 and alarming differences in complication rates between weekdays and weekends in obstetric units, 4 but the drivers of this variation remain incompletely characterised. In recent years, large studies have found null associations between obstetric processes of care and quality metrics, 5 and between recently adopted quality measures (ie, elective early-term delivery) and perinatal morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to evaluate whether differences in outcomes exist between hospitals with different professional models because increasing evidence suggests that rates of obstetric interventions vary widely across hospitals and are not explained by patient risk factors. 5,6 …”
Section: Introductionmentioning
confidence: 99%